GAMBARAN KADAR TRIGLISERIDA PADA REMAJA OBES DI KABUPATEN MINAHASA - Damanik, Novelina Irianti; Manampiring, Aaltje E.; ., Fatimawali (Universitas Sam Ratulangi, 2013)
Abstract: Obesity is a condition with abnormal fat accumulation or excessive adipose tissue that can be detrimental to health. Central obesity has a strong correlation with insulin resistance. In a state of insulin resistance hormone sensitive lipase in adipose tissue becomes active so that triglycerides in adipose tissue lipolysis increases. Therefore, insulin resistance occurs abnormalities of serum lipid profiles a typical triglyceride levels increased. The purpose of this study was to describe the levels of triglycerides in obese adolescents in Tondano City. Cross-sectional study has been done in August 2012- January 2013 with population of the student in the SMK Negeri in Tondano city, from grade one to grade three were aged 13-18 years with a simple random sampling as the technique of sampling. Measurements of weight, height, waist circumference and triglyceride levels examinations have been made. Obesity is declared if it meets the following criterias: BMI ≥ 25 kg/m2, waist circumference > 90 cm for men and > 80 cm for women. Triglyceride levels increased when ≥ 150 mg / dl. Found in 54 samples of patients with obesity. 54 obese patients were consist of female (43 samples, 79.63%), men (11 samples, 20.37%). 54 samples were measured, eight samples had elevated levels of triglycerides are women (7 samples, 88%) and men (1 samples, 12%). Conclusion of this study found that obese women have experienced more elevated triglyceride levels than obese men. These results may be useful for prevention and treatment of obesity and elevated triglyceride levels in the early teens. Key words: adolescent, obesity, triglyceride. Abstrak: Obesitas merupakan suatu keadaan dengan akumulasi lemak yang tidak normal atau berlebihan di jaringan adiposa sehingga dapat mengganggu kesehatan. Obesitas sentral mempunyai korelasi yang kuat dengan resistensi insulin. Pada keadaan resistensi insulin hormone sensitive lipase di jaringan adiposa akan menjadi aktif sehingga lipolisis trigliserida di jaringan adiposa semakin meningkat. Oleh karena itu pada resistensi insulin terjadi kelainan profil lipid serum yang khas yaitu kadar trigliserida meningkat. Tujuan dari penelitian ini adalah untuk mengetahui gambaran kadar trigliserida pada remaja obes di Kota Tondano. Penelitian potong lintang di lakukan Agustus 2012- Januari 2013 dengan populasi siswa SMK Negeri di Kota Tondano dari kelas satu sampai kelas tiga yang berumur 13-18 tahun dengan teknik pengambilan sampel simple random sampling. Dilakukan pengukuran berat badan, tinggi badan, lingkar pinggang dan pemeriksaan kadar trigliserida. Obesitas dinyatakan apabila memenuhi kriteria sebagai berikut: IMT ≥25 kg/m2, lingkar pinggang >90 cm untuk laki-laki dan >80 cm untuk perempuan. Kadar trigliserida meningkat apabila ≥150 mg/dl. Didapatkan 54 sampel penderita obesitas. 54 penderita obesitas adalah perempuan (43 sampel; 79,63%), laki-laki (11 sampel; 20,37%). 54 sampel yang diukur, 8 sampel yang mengalami peningkatan kadar trigliserida yaitu perempuan (7 sampel; 88%) dan laki-laki (1 sampel; 12%). Kesimpulan penelitian ini didapatkan perempuan yang obesitas lebih banyak mengalami peningkatan kadar trigliserida di bandingkan laki-laki yang obesitas. Hasil ini dapat berguna untuk tindakan pencegahan dan tatalaksana obesitas serta peningkatan kadar trigliserida pada remaja sejak dini. Kata kunci: remaja, obesitas, trigliserida.